Technological Innovation Model In Implementing E-Marketing For MSMEs In East Kalimantan - Tikawati Tikawati; Sugiono Sugiono; Siti Qomariah (International Journal of Social Service and Research, 2023)
The world is experiencing significant changes in information and communication technology development, making e-marketing a very critical method to implement. The open competition requires MSMEs in the regions to pay more attention to marketing aspects via the Internet as a modern marketing medium that is more profitable and closer to customers. Studies on the implementation of e-marketing in MSMEs still need to be completed, especially in developing countries like Indonesia, where MSMEs are very large and are one of the supporting sectors in increasing state income. This research examines the influence of technological, organisational, environmental (TOE) and individual contexts on the implementation of e-marketing for MSMEs in East Kalimantan. The results show that the technical and ecological context positively influences the performance of e-marketing in East Kalimantan. In contrast, organisational and individual variables do not affect the implementation of e-marketing for MSMEs in East Kalimantan.